Statistical theory of fullerite solubility - Ayaganov, Zh.E.; Gabdullin, M.T.; Schur, D.V.; Ismailov, D.V.; Kerimbekov, D.S.; Batryshev, D.G.; Ciuparu, D. (Recent Contributions to Physics, 2019)
In this paper, calculated the solubility of fullerite in order to clarify the features of the temperature dependence in the process. This takes into account the implementation in different temperature ranges of the crystalline structures of fullerite formed by fullerene molecules of various modifications. Experimental studies of solutions of fullerene molecules in various organic media made it possible to establish the features of the temperature dependence of the solubility of fullerite C60. Instead of the expected increase in solubility with increasing temperature, the extremes of its temperature dependence with a maximum at room temperature were revealed, the endothermicity of the dissolution process was established. The anomalies of the temperature dependence of the solubility of fullerenes C60 in organic matrices are due to a change in the structure of bonds in the framework of fullerene molecules, which, in turn, affect the structure of solid-phase fullerite. More accurate results using the formulas obtained can be calculated if the true values of the energy parameters are known from independent experiments. However, it can be assumed that the nature of the revealed patterns will remain.